Methodologies for the investigation of corroded iron objects: examples from prehistoric sites in South-eastern Arabia and Western Iran. Issue 2 (15th December 2017) - Stepanov, Ivan; Weeks, Lloyd; Franke, Kristina; Cable, Charlotte; Overlaet, Bruno; Magee, Peter; Händel, Marc; Aali, Yaaqoub Yousif Al; Radwan, Mansour Boraik; Zein, Hassan
ABSTRACT: Ancient iron objects from early Iron Age archaeological sites are almost always severely corroded, which can severely limit the possibilities for their archaeometallurgical analysis. In this paper, a range of corroded iron objects from different sites and regions of the ancient Near East are investigated with the purpose of developing an integrated scientific approach to the investigation of such materials, outlining the capabilities and major technical limitations of currently available techniques. Specific objectives of the research include: (1) Assessing the state of degradation of ancient ferrous objects in respect to the portion of remnant carburized areas preserved; (2) Identifying metallographic structures and evaluating the carbon content from the observation of remnant carburized areas; (3) Developing an understanding of the representativeness of remnant carburized areas in corroded ferrous samples; and (4) Exploring the validity and technical constraints of SEM-EDS analyses of slag inclusions in corroded iron artefacts for the determination of provenance. GRAPHICAL ABSTRACT: